Lipoprotein (a) Testing and Changes in Lipid-Lowering Therapy in Patients With ASCVD: Findings From the cvMOBIUS-2 Registry - Nishant P. Shah; Peter Shrader; Nikki Freeman; Satoshi Shoji; Cezary Wojcik; Laney K. Jones; John N. Booth; Eric D. Peterson; Ann Marie Navar (Circulation: Population Health and Outcomes, 2026)
BACKGROUND: Although the effectiveness of Lp(a) (lipoprotein[a])–lowering therapies remains under study, lipid guidelines now recommend Lp(a) testing in all adults to identify individuals who need more aggressive risk factor modification. Therefore, we evaluate contemporary patterns of Lp(a) testing and the impact of testing on LDL-C (low-density lipoprotein cholesterol) management. METHODS: Electronic health record patient data from 13 US health systems from January 1, 2021 to January 1, 2025, were utilized to assess the annual proportion of patients with atherosclerotic cardiovascular disease who underwent Lp(a) testing. Multivariable logistic regression was used to identify factors associated with (1) Lp(a) testing and (2) high Lp(a) (≥125 nmol/L or ≥50 mg/dL). Changes in lipid-lowering therapy after Lp(a) testing were evaluated, stratified by Lp(a) level. RESULTS: Among 1 948 540 patients with atherosclerotic cardiovascular disease (44% female sex; mean age, 70.9±12.8 years), 36 410 (1.9%) had an Lp(a) test. Testing increased slightly over time but remained low: from 0.2% in 2021 to 0.8% in 2024. Among tested patients, 31.1% had elevated Lp(a). Although female sex (odds ratio, 0.95 [95% CI, 0.93–0.98]) and non-Hispanic Black patients (0.79 [95% CI, 0.76–0.82]) were less likely to undergo testing, these groups had higher odds of elevated Lp(a) (1.19 [95% CI, 1.14–1.25] and 2.83 [95% CI, 2.63–3.05], respectively). Intensification of lipid-lowering therapy in those with LDL-C≥55 mg/dL increased with higher Lp(a) levels: 32.7% with Lp(a) 125 to